The Art of Abduction (The MIT Press, 2022)
A novel defense of abduction, one of the main forms of nondeductive reasoning. With this book, Igor Douven offers the first comprehensive defense of abduction, a form of nondeductive reasoning. Abductive reasoning, which is guided by explanatory considerations, has been under normative pressure since the advent of Bayesian approaches to rationality. Douven argues that, although it deviates from Bayesian tenets, abduction is nonetheless rational. Drawing on scientific results, in particular those from reasoning research, and using computer simulations, Douven addresses the main critiques of abduction. He shows that versions of abduction can perform better than the currently popular Bayesian approaches-and can even do the sort of heavy lifting that philosophers have hoped it would do. Douven examines abduction in detail, comparing it to other modes of inference, explaining its historical roots, discussing various definitions of abduction given in the philosophical literature, and addressing the problem of underdetermination. He looks at reasoning research that investigates how judgments of explanation quality affect people's beliefs and especially their changes of belief. He considers the two main objections to abduction, the dynamic Dutch book argument, and the inaccuracy-minimization argument, and then gives abduction a positive grounding, using agent-based models to show the superiority of abduction in some contexts. Finally, he puts abduction to work in a well-known underdetermination argument, the argument for skepticism regarding the external world.